2013
DOI: 10.5271/sjweh.3384
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of recurrent sickness absence among workers having returned to work after sickness absence due to common mental disorders

Abstract: Predictors of recurrent sickness absence among workers having returned to work after sickness absence due to common mental disorders by Arends I, van der Klink JJL, van Rhenen W, de Boer MR, Bültmann U A broad range of possible predictors of recurrent sickness absence (SA) among workers with common mental disorders (CMD) is investigated over 12 months follow-up. The results show that work-related factors, especially conflicts with supervisor and company size >100 employees, rather than disease-related factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
3
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 37 publications
(50 reference statements)
2
41
3
4
Order By: Relevance
“…This holds in particular for MDD, because of its long-term course with different levels of residual or subclinical symptoms, a high rate of recurrence (ten Doesschate et al, 2010;Hardeveld et al, 2010) and sickness absence Endo et al (2012). However, studies focusing on these outcomes are scarce (Hees et al, 2013(Hees et al, , 2012Virtanen et al, 2011;Arends et al, 2014). Moreover, previous studies on the relationship between depression and work functioning did not distinguish between patients with MDD and patients with MDD in remission, or only focused on specific category of predictors (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…This holds in particular for MDD, because of its long-term course with different levels of residual or subclinical symptoms, a high rate of recurrence (ten Doesschate et al, 2010;Hardeveld et al, 2010) and sickness absence Endo et al (2012). However, studies focusing on these outcomes are scarce (Hees et al, 2013(Hees et al, , 2012Virtanen et al, 2011;Arends et al, 2014). Moreover, previous studies on the relationship between depression and work functioning did not distinguish between patients with MDD and patients with MDD in remission, or only focused on specific category of predictors (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…The mean age was significantly higher in subjects with at least one chronic disease than in those without (49±7.5 vs. 44±8.1 years; p < 0.01). Conversely, job seniority was similar between employees affected and not affected by chronic conditions (16)(17)(18)(19)(20)(21)(22)(23) vs. 19 (IQR 11-26) years; p = 0.1).…”
Section: General Characteristics Of the Study Populationmentioning
confidence: 99%
“…Furthermore, most of the previous investigations addressed the effect of a single chronic disease on sickness absence [21][22][23]. In a prospective cluster-randomized controlled trial of 158 subjects, Arends et al [23] focused on workers with psychiatric disorders, demonstrating that medication, company size, and conflicts with supervisor predicted the incidence of recurrent sickness absence. By contrast, surveys exploring the total burden of chronic diseases on sickness absence are less common.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the duration of financial compensation plays an important role in relation to sickness presenteeism. Arends et al reported that the incidence of relapse of mental illness became greater as the size of company increased 25) , and Rost et al reported that the economic impact of a loss in productivity varies according to company size 26) . In the present study, no relationship was observed between sickness presenteeism and company size.…”
Section: Discussionmentioning
confidence: 99%